Advanced methods in distance education : applications and practices for educators, administrators, and learners - Dooley, Kim E., 1961- 4 0 16; Lindner, James R.,;Dooley, Larry McCoy; 5 (Hershey, PA : Information Science Publishing, 2005)
This book covers theory to practice, with readers gaining the necessary knowledge, skills, and abilities to be successful in teaching or training using technology-mediated instruction.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Distance education.;Educational technology. -- 20; 20; 2